Systematic reviews and maps as tools for applying behavioral ecology to management and policy. (8th October 2018) - Berger-Tal, Oded; Greggor, Alison L; Macura, Biljana; Adams, Carrie Ann; Blumenthal, Arden; Bouskila, Amos; Candolin, Ulrika; Doran, Carolina; Fernández-Juricic, Esteban; Gotanda, Kiyoko M; Price, Catherine; Putman, Breanna J; et al.
Abstract : We describe the utility of conducting formal systematic reviews and maps to synthesize behavioral evidence in a way that enhances its utility to managers, policy makers, and other stakeholders. Similar to the evidence-based revolution in medicine, the application of formal systematic review processes has the potential to invigorate the field of behavioral ecology and accelerate the uptake of behavioral evidence in policy and management. Abstract: Although examples of successful applications of behavioral ecology research to policy and management exist, knowledge generated from such research is in many cases under-utilized by managers and policy makers. On their own, empirical studies and traditional reviews do not offer the robust syntheses that managers and policy makers require to make evidence-based decisions and evidence-informed policy. Similar to the evidence-based revolution in medicine, the application of formal systematic review processes has the potential to invigorate the field of behavioral ecology and accelerate the uptake of behavioral evidence in policy and management. Systematic reviews differ from traditional reviews and meta-analyses in that their methods are peer reviewed and prepublished for maximum transparency, the evidence base is widened to cover work published outside of academic journals, and review findings are formally communicated with stakeholders. This approach can be valuable even when the systematic literature search fails to yield sufficient evidence for a full review or meta-analysis; preparing systematic maps of the existing evidence can highlight deficiencies in the evidence base, thereby directing future research efforts. To standardize the use of systematic evidence syntheses in the field of environmental science, the Collaboration for Environmental Evidence (CEE) created a workflow process to certify the comprehensiveness and repeatability of systematic reviews and maps, and to maximize their objectivity. We argue that the application of CEE guidelines to reviews of applied behavioral interventions will make robust behavioral evidence easily accessible to managers and policy makers to support their decision-making, as well as improve the quality of basic research in behavioral ecology.